HEALTH SECTOR DECENTRALIZATION AND ITS IMPLICATION TO HEALTH SERVICES IN INDONESIA - Aderia Rintani; Adik Wibowo (Faculty of Public Health, Sriwijaya University, 2019)
Background: After more than a decade, in what way decentralization has affected health service and population health status in Indonesia, is still partly known. This paper aims to review about to what extent the health sector decentralization has affected health services in Indonesia, especially in access and health systems management. Methods: We conducted systematic search studies using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). We search for relevant studies using keywords 'decentralization' OR 'decentralisation' AND '(public health)' AND 'effect' OR 'impact' AND 'reform' AND '(health inequalities)' AND 'Indonesia' on electronic sources Proquest, Science Direct, and EBSCOHost. The articles then filtered using pre determined criterias and duplication removal. Results: Database search resulting on 628 articles in Proquest, 0 articles in Science Direct, and 13 articles in EBSCOHost. The screening result were 5 eligible articles. We found equality of access in health services were jeopardized by fragmented health services and worsen health disparities among districts that occured after decentralization. This worsen gap between the most developed provinces of Java-Bali and those of other island groupings affected the community's health status. Low local government's capacity in planning, managing and utilizing health resources were the most reported evidence in decentralized health system. Conclusion: This study concludes that good capacity of local government, coordination and monitoring system between central and local government, partnership with private sectors and community empowerment are essential to achieve better health outcome result in decentralized Indonesia.